Application and fallibility of Artificial Intelligence and machine learning in Diagnostic Pathology - Mishra, Pallavi; Panda, Abikshyeet; Mahapatra, Monalisha; Dakshinakabat, Prachurya; Mohanty, Aishwariya; Bhuyan, Lipsa (Bangladesh Journal of Medical Science, 2024)
Artificial intelligence (AI) refers to the use of technology and computers to replicate behavioral intelligence and analytical reasoning that is equivalent to that of a human being. The medical sciences make substantial use of computer systems with artificial intelligence which primarily include remote patient treatment, prescription recording, increasing doctor-patient interaction, medication discovery and patient diagnosis. Its application in health care industry is mainly because of increased job demands, difficult tasks, and probable doctor weariness all have the potential to impair diagnostic performance. In this review we have enlightened the various roles of AI such as automated diagnosis, predictive analysis, image analysis, precision medicine and the biomarker development. The use of AI tools in pathology has grown significantly in recent years, and it is predicted that they will revolutionize the field in the years to come. AI tools can change how pathology functions while rendering it more efficient at meeting the demands of the modern era of precision medicine. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S32-S37